Waste Treatment and Resource Utilization: Removal and recovery of soluble impurities from nitric acid leaching residue of phosphate rock by electrokinetic. (1st May 2023) - Chen, Bangjin; Jin, Caiyue; Qu, Guangfei; Yang, Jieqian; Liu, Ye; Qin, Jin; Kuang, Lingrui; Li, Hailin; He, Minjie; Dan, Yue
Abstract: Electrodynamic cleaning techniques for removing and recycling soluble impurities (phosphorus, fluorine, Sr, Pb, Cr, Cu, and Mn) in nitric acid leaching residues of phosphate rock (NG) were investigated. The PO4 3− concentration of the anode chamber was increased to 207.94 mg/L, while the F − concentration of the cathode chamber rose to 28.33 mg/L. Besides, the soluble phosphorus levels in the cathode regions (R1 and R2) were decreased by 98.02% and 90.16%, respectively. Moreover, the dissolved heavy metals, namely Mn, Cr, Cu and Pb in NG were enriched in the anode chamber, and Sr was enriched in the cathode chamber. The synergistic effects of electrocoagulation and electrodeposition lowered the levels of phosphate, fluoride, and heavy metals in the cathode, thus reducing the decreasing electrical conductivity. The migration and accumulation behaviors of soluble impurities in an electric field were regulated by electromigration, electro-osmotic flow, and electrolysis reaction. Considering that, this paper provides support for the harmless treatment of NG and the recovery of valuable elements, which is conducive to developing the wet-process phosphoric acid process and reducing the large-scale storage of phosphogypsum.